2000
DOI: 10.1042/cs19990232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine receptor antagonists on the responses to contrast media in the isolated rat kidney

Abstract: Contrast media can induce both a decrease in renal blood flow and a reduction in glomerular filtration rate (GFR) when administered to both experimental animals and humans. In the present study we have examined the role of adenosine in mediating these effects using the isolated perfused rat kidney. Kidneys were perfused with a 6. 7%-(w/v)-albumin-based perfusate supplemented with glucose and amino acids (n=6 per group). They were exposed to diatrizoate [20 mg of iodine (mgI)/ml; osmolality 1650 mOsm/kg of wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Kolonko et al (1998) stated that highosmolar contrast medium induced impairment of renal excretory, endocrine and tubular function could be prevented by giving pre-treatment with theophylline. The study of Oldroyd et al (2000) found that urografin produced a fall in GFR and renal perfusate flow (RPF) and theophylline prevented the fall in GFR but did not affect the decreases in RPF. They suggested a role for adenosine acting at the A1 receptor in mediating the decrease in GFR induced by contrast dye.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolonko et al (1998) stated that highosmolar contrast medium induced impairment of renal excretory, endocrine and tubular function could be prevented by giving pre-treatment with theophylline. The study of Oldroyd et al (2000) found that urografin produced a fall in GFR and renal perfusate flow (RPF) and theophylline prevented the fall in GFR but did not affect the decreases in RPF. They suggested a role for adenosine acting at the A1 receptor in mediating the decrease in GFR induced by contrast dye.…”
Section: Discussionmentioning
confidence: 99%
“…During oxygen deficiency or during increased tubular transport work the rate of adenosine formation is enhanced. Experiments on laboratory animals clearly show that it acts as a vaso-constrictive metabolite in the kidney so decreases GFR by constricting afferent arterioles via A1 receptors, especially in superficial nephrons, and thus lowers the salt load and transport work of the kidney (Jenik et al, 2000;Oldroyd et al, 2000 ;Osswald et al,1995). On contrary, it leads to vasodilation via A2 receptors in the deep cortex and exerts differential effects on sodium chloride transport along the tubular and collecting duct system (Arakawa et al, 1996 ;Vallon and Osswald, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…CM osmotically irritate tubular cells, leading to increased adenosine triphosphate turnover and subsequent release of adenosine 23 . In contrast with other tissues in which adenosine can lead to hyperemia, in the kidney it causes vasoconstriction of the vas efferens by way of the adenosine‐1 receptor and a reduction in renal plasma flow and glomerular filtration rate 32, 33 . Adenosine also briefly stimulates the adenosine‐2 receptor, albeit to a lesser degree and mostly in the vas efferens.…”
Section: Discussionmentioning
confidence: 99%
“…Existen varias alteraciones intrarrenales y sistémicas a las que se les ha atribuido cierto papel en la fisiopatología de la IRA consecutiva a la administración de medios de contraste radiológico yodados. Quizás la más estudiada sea la fuerte elevación del nivel plasmático de adenosina, 25,26 después de la administración de medios de contraste yodados, que estimula tanto receptores A2 (lo que induce vasodilatación inicial) como A1 (lo que lleva a vasoconstricción sostenida). 24,26 Se considera que estos efectos antagónicos son los que inician la reacción bifásica inicial del riñón ante la noxa química (Figura n.º 1).…”
Section: Patogénesisunclassified